Examining The Function Of Universal Health Coverage In The Framework Of Global Health Security For Pandemic preparedness and response (Journal of Namibian Studies : History Politics Culture, 2022)
A number of international initiatives, such as plans for a pandemic treaty, a Pandemic Fund, and procedures for fair access to medical countermeasures, have been created in response to the COVID-19 pandemic in an effort to improve and restructure the global architecture for pandemic preparedness and response. These programs aim to close gaps in health security and traditional public health functions, thereby leveraging important lessons learned from the ongoing pandemic. However, the critical role of universal health coverage in sustainably reducing outbreaks and the significance of strong primary health care in effectively and fairly protecting communities from future health threats have not received enough attention. The global community should avoid making the same mistakes in previous health security initiatives that ultimately aided in the COVID-19 pandemic's quick spread and disproportionately impacted marginalized and vulnerable groups, particularly by undervaluing the significance of cohesive, multisectoral health systems. This Health Policy paper identifies opportunities to rethink health security by expanding universal health coverage and highlights significant (though frequently overlooked) gaps in pandemic preparedness and response that apply to larger health emergency preparedness and response efforts. After that, we provide a thorough set of suggestions to guide the creation of important pandemic preparedness and response plans in three areas: financing, governance, and supporting projects. We seek to provide practical solutions that fairly address the needs of all communities while guaranteeing resilience to future pandemic threats by identifying strategies that simultaneously strengthen health systems through universal health coverage and global health security.